Contacts, Credibility and Common Knowledge : Their Influenceon Inflation Convergence - Miller, Marcus (IMF Working Papers; Working Paper ;, 1992)
In this paper three possible reasons are examined for a sluggish inflation response to a hard currency peg. Models of overlapping wage contracts are analyzed and shown to generate little inertia. This contrasts with the effects of government credibility and the speed of private sector learning, which are shown to have a major impact on the speed of inflation adjustment. But even if individual agents believe the government will not devalue, it is shown that inflation inertia can still arise if these expectations are not common knowledge.